FREQUENCY OF POST-OPERATIVE FAECAL INCONTINENCE IN PATIENTS WITH CLOSED AND OPEN INTERNAL ANAL SPHINCTEROTOMY - Ghayas, Nighat; Younus, Syed Muneeb; Mirani, Abdul Jabbar; Ghayasuddin, Mohammed; Qazi, Amna; Suchdev, Sunil Dutt; Bakshi, Saqib Kamran (Journal of Ayub Medical College Abbottabad, 2015)
Background: Fissure in ano is one of the commonest benign and painful proctologic diseases causing considerable morbidity and reduction in quality of life. There are medical as well as surgical treatment options for anal fissure. The study was conducted to compare the frequency of postoperative faecal incontinence in patients with closed lateral internal anal sphincterotomy with von-greaves knife versus standard Park’s operation (open method) for chronic anal fissure. Methods: This was a randomized controlled trial (RCT) was conducted at the Department of Surgery, KVSS, S.I.T.E. Hospital, Karachi, for a period of six months from 13th February to 12th August 2011. Ninety four consecutive patients having chronic anal fissure were assigned through blocked randomization to groups A & B, with 47 patients in each group. Closed lateral internal anal sphincterotomy (CLIAS) via von-greaves knife was carried out in patients of group-A whereas patients of group-B were subjected to open internal anal sphincterotomy (OIAS) also known as Parks’ procedure. Faecal incontinence was noted on the 5th post-operative day. Data was analysed using SPSS 16. Results: There were 81 (86.2%) males and 13 (13.8%) females with male to female ratio being 6:1. Mean age was 38.38 mp±14.56 years. Post-operative faecal incontinence in patients undergoing CLIAS was 4.3% while it was 21.3% in those undergoing OIAS with a p-value of 0.027. CLIAS with von-greaves knife is effective in reducing faecal incontinence on 5th postoperative day as compared to standard OIAS. Conclusion: CLIAS with von-greaves knife is effective in reducing faecal incontinence on 5th postoperative day as compared to OIAS (Park’s procedure). Therefore, this technique may be used in future regularly to treat chronic anal fissure for prevention of this morbidity.